2017
DOI: 10.1001/jamasurg.2017.1720
|View full text |Cite
|
Sign up to set email alerts
|

Association of Expanded Medicaid Coverage With Hospital Length of Stay After Injury

Abstract: Expanded Medicaid eligibility is associated with shorter hospital LOS in mildly injured Medicaid recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The observed increase in LOS in our study was negated after removing Maryland from the analysis, mirroring previous studies that have found that changes in LOS among trauma patients after Medicaid expansion varied by state and injury severity. 8 , 25 , 59 , 60 The paucity of post-discharge care facilities in some regions can create a bottleneck for patients awaiting discharge to these specialized services and, when combined with variation across states and hospitals over time in decision making about admitting vs observing nonseverely injured patients, contributes to variability in LOS among admitted trauma patients. 61 In contrast, the difference in reported access to home healthcare is likely a result of study cohort selection.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in LOS in our study was negated after removing Maryland from the analysis, mirroring previous studies that have found that changes in LOS among trauma patients after Medicaid expansion varied by state and injury severity. 8 , 25 , 59 , 60 The paucity of post-discharge care facilities in some regions can create a bottleneck for patients awaiting discharge to these specialized services and, when combined with variation across states and hospitals over time in decision making about admitting vs observing nonseverely injured patients, contributes to variability in LOS among admitted trauma patients. 61 In contrast, the difference in reported access to home healthcare is likely a result of study cohort selection.…”
Section: Discussionmentioning
confidence: 99%
“…California is 1 of only 32 states that participated in Medicaid expansion, and despite initial evidence to date of improved hospital revenues as a consequence of insurance gains, further study is required both at local and national levels in order to better understand the implications of recent and forthcoming changes in policy. 17,20 Another objective of insurance expansion legislation was to improve quality of health care, but the impact on quality of injury-related care is still being elucidated. Disparities in health outcomes based on insurance status are established in surgery and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…8 Individual studies have shown that expansion also correlates with declines in non-emergent use of the emergency department 9 and lengths of hospital stays. 10,11 Yet Medicaid expansion is no panacea. Many providers are reluctant to accept new Medicaid patients due to low reimbursement rates, which can limit de facto access to care.…”
Section: Millions Of People Are Still Uninsuredmentioning
confidence: 99%